Congenital syndromes of pain and painlessness - Woods, Geoff; Cox, James (Henry Stewart Talks, 2014)
What is pain?, How much pain is someone suffering?, What is the use of pain?, Pain pathways, Types of pain (Nociceptive, Inflammatory, Neuropathic, mixed), Primary erythromelalgia, Mutations in SCN9A cause erythromelalgia, Voltage-gated ion channels, Paroxysmal extreme pain disorder (familial rectal pain), Mutations in SCN9A cause PEPD, Congenital insensitivity to pain, SCN9A gene map, Electrical activity of wild type versus mutant constructs, Low-copy number vector = pcDNA3JC, Exon 6 splice variants, Neuropathies HSANs, Rita Levi Montalcini, TRKA signalling, Hereditary autonomic and sensory neuropathy type 4 (HSAN4), HSAN5, NGFB, Familial dysautonomia, Treatment of pain, Mendelian disorders of pain, Update talk: Congenital insensitivity to pain, Update talk: Genetic pain loss disorders and associated mutations, Update talk: Hereditary sensory neuropathy, Update talk: Hereditary sensory and autonomic neuropathy, Update talk: FAAH-OUT-associated pain insensitivity, Update talk: Mutated genes as potential analgesic drug targets, Update talk: Painful genetic disorders
Updated at 2024/02/29